NTRK gene fusions in melanoma: detection, prevalence and potential therapeutic implications. (12th July 2020) - Forschner, Andrea; Forchhammer, Stephan; Bonzheim, Irina
Summary: Fusions involving neurotrophic tyrosine receptor kinase (NTRK) are known drivers of oncogenesis and also occur in melanoma, although very rarely. A particularly high incidence of NTRK gene fusions is reported in infantile fibrosarcoma (> 90 %) or the secretory type of breast cancer (> 90 %). Recently, larotrectinib (a tropomyosin receptor kinase [TRK] inhibitor) was approved, and we wondered whether TRK inhibitors might also be helpful for melanoma patients. We therefore screened the literature and obtained relevant results. NTRK fusions are relatively common in spitzoid melanoma, with a prevalence of 21–29 % compared to < 1 % in cutaneous or mucosal melanoma and 2.5 % in acral melanoma. It appears that fusion proteins are mutually exclusive for most common oncogenic drivers such as BRAF or NRAS. A further indicator of an increased probability of detecting NTRK‐positive tumors could be a low mutation load. Since TRK inhibitors are already available for patients with NTRK fusions, the challenge will be to implement screening for NTRK gene fusions in clinical practice. A possible approach could be to screen BRAF, NRAS and KIT wild‐type melanoma patients with next‐generation sequencing as soon as they need systemic treatment or at the latest when they have no tumor control on checkpoint inhibitors.